Interdisciplinary engineering education: A review of vision, teaching, and support - Van den Beemt, Antoine; MacLeod, Miles; Van der Veen, Jan; Van de Ven, Anne; Baalen, Sophie; Klaassen, Renate; Boon, Mieke (Journal of engineering education (Washington, D.C.), 2020)
Background Societal challenges that call for a new type of engineer suggest the need for the implementation of interdisciplinary engineering education (IEE). The aim of IEE is to train engineering students to bring together expertise from different disciplines in a single context. This review synthesizes IEE research with a focus on characterizing vision, teaching practices, and support. Purpose We aim to show how IEE is conceptualized, implemented, and facilitated in higher engineering education at the levels of curricula and courses. This aim leads to two research questions: What aspects of vision, teaching, and support have emerged as topics of interest in empirical studies of IEE? What points of attention regarding vision, teaching, and support can be identified in empirical studies of IEE as supporting or challenging IEE? Scope/Method Ninety‐nine studies published between 2005 and 2016 were included in a qualitative analysis across studies. The procedure included formulation of research questions, searching and screening of studies according to inclusion/exclusion criteria, description of study characteristics, appraisal, and synthesis of results. Conclusions Challenges exist for identifying clear learning goals and assessments for interdisciplinary education in engineering (vision). Most pedagogy for interdisciplinary learning is designed to promote collaborative teamwork requiring organization and team management. Our review suggests that developing interdisciplinary skills, knowledge, and values needs sound pedagogy and teaming experiences that provide students with authentic ways of engaging in interdisciplinary practice (teaching). Furthermore, there is a limited understanding of what resources hinder the development of engineering programs designed to support interdisciplinarity (support).